Hubungan antara Aktivitas Fisik dan Status Gizi sebagai Faktor Risiko Penyakit Tidak Menular (Hipertensi dan Diabetes Melitus) pada Wanita Usia Produktif - Laras Eka Nur Hasanah; Fadean Stefany; Dwi Intan Pakuwita AR (Universitas Muhamadiyah Manado, 2026)
This study aimed to examine the association between physical activity and nutritional status as risk factors for noncommunicable diseases among women of reproductive age. A descriptive quantitative study with a cross-sectional approach was conducted in Kranggan Village involving 35 respondents selected through purposive sampling. Data on physical activity were collected using questionnaires, while nutritional status was assessed based on Body Mass Index (BMI). The findings showed that most respondents had moderate physical activity levels (51.4%), followed by low physical activity levels (42.8%). Regarding nutritional status, the majority of respondents were classified as overweight (51.4%) and obese (28.6%). Statistical analysis demonstrated a significant relationship between physical activity and nutritional status (p = 0.003). The results indicate that inadequate physical activity is associated with increased nutritional status problems, particularly overweight conditions. Therefore, low physical activity and excessive body weight represent interconnected risk factors contributing to the development of noncommunicable diseases among women of reproductive age. This study highlights the importance of promoting regular physical activity and maintaining balanced nutritional status as preventive strategies to reduce the risk of noncommunicable illnesses.